Rainfall Shocks, Local Revenues, and Intergovernmental Transfer in Mali. (February 2015) - Sanoh, Aly
Summary: This paper explores the implications of rainfall shocks for municipal tax revenues and intergovernmental transfers in Mali. I found that exogenous phenomena such as weather, not under the control of local actors, could affect the way de facto decentralization plays out by influencing the fiscal capacity of local governments. In a panel data of 692 municipalities from 2000 to 2008, I found that rainfall shocks, through the fluctuations they induce in agricultural incomes, affect revenue collection of local governments, and in turn drive further revenues local governments receive through transfer by the central government.